Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Enzyme immobilization on epoxy supports in reverse micellar media: prevention of enzyme denaturation - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Yalangi; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Journal of Molecular Catalysis B-Enzymatic, 2012)
Immobilization of enzymes such as alpha-chymotrypsin (EC 3.4.21.1), yeast alcohol dehydrogenase (YADH) from Saccharomyces cerevisiae (EC 1.1.1.1) and glucose dehydrogenase (GDH) from Gluconobacter cerinus (EC 1.1.1.119) has been carried out. Copolymers of allyl glycidyl ether (AGE) crosslinked with 25% ethylene glycol dimethacrylate (EGDM) (25 mg, dry wt) were contacted with the enzymes solubilized in reverse micellar media (0.5-5 mg/mL)(overall) of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) salt in isooctane, and cetyl trimethylammonium bromide (CTAB) in chloroform-isooctane (50:50, v/v). Although the enzymes are readily denatured (>90%) after adsorption on the copolymer in aqueous buffers, no such adsorption-induced denaturation takes place in reverse micelles. alpha-Chymotrypsin is remarkably stable in AOT reverse micelles when 0.025 M citrate buffer of pH 9.0 containing 2 mM CaCl2 is used in the water pools instead of Tris-HCl buffer of pH 8.5. It was possible to achieve enzyme concentration of 5 mg/mL in 0.3 M AOT at molar ratio of water to surfactant, (W-0), 30 and to obtain alpha-chymotrypsin loading of 20 mg/g of copolymer. The recovered enzyme solution can be reused with a fresh batch of polymer after supplementing the depleted solution. The immobilized enzyme exhibits excellent stability in aqueous buffers at room temperature and can be recycled several times. YADH is stable in both AOT and CTAB reverse micelles while GDH is stable only in CTAB reverse micelles containing 0.05 M Tris-HCI buffer of pH 8.5. Interestingly, the combination of YADH (2.5 mg/g) and GDH (0.5 mg/g) co-immobilized on the copolymer using CTAB-chloroform-isooctane system can be used for regeneration and recycle of NADPH at least 50 times as exemplified by complete reduction of a prochiral ketoester, ethyl 4-phenyl-2,4-dioxobutyrate (10 mM) to ethyl (R)-2-hydroxy-4-phenylbutyrate (HPB ester) using NADPH (0.2 mM). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: allyl glycidyl ether; alpha-Chymotrypsin; ethylene glycol dimethacrylate; Glucose dehydrogenase; Reverse micelles; Yeast alcohol dehydrogenase

Co-immobilized glucose oxidase and beta-galactosidase on bovine serum albumin coated allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer as a biosensor for lactose determination in milk - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Ponrathnam, Surendra (Enzyme and Microbial Technology, 2014)
Bovine serum albumin (BSA) was adsorbed on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) at pH 8.0 (16% w/w). The amino, thiol and carboxylic acid functional groups available on protein coated surface were utilized for covalent immobilization of glucose oxidase and beta-galactosidase, both independently, and in a step-wise manner on the same matrix, with no more than 10% loss of enzyme activity during immobilization. Glutaraldehyde cross-linking after immobilization provided stable enzyme preparations. The pH-optima of the immobilized enzymes were similar to those for free enzyme but their thermal stability was vastly improved. The co-immobilized enzyme support was used as a biosensor for determination of lactose in milk with excellent reproducibility and reusability. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: beta-Galactosidase; Bovine serum albumin; Glucose oxidase; Immobilization; Lactose assay

Comparison of polymer induced and solvent induced trypsin denaturation: the role of hydrophobicity - Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2014)
Trypsin adsorption from aqueous buffer by various copolymers of allyl glycidyl ether-ethylene glycol dimethacrylate (AGE-EGDM) copolymer with varying crosslink density increases with increasing crosslink density and the effect slowly wears off after reaching a plateau at 50% crosslink density. The copolymer with 25% crosslink density was reacted with different amines with alkyl/aryl side chains to obtain a series of copolymers with 1,2-amino alcohol functional groups and varying hydrophobicity. Trypsin binding capacity again increases with hydrophobicity of the reacting amine and a good correlation between logP(octanol) of the amine and protein binding is observed. The bound trypsin is denatured to the extent of 90% in spite of the presence of hydrophilic hydroxyl and amino groups. The behavior was comparable to that in mixtures of aqueous buffer and water-miscible organic co-solvents where the solvent concentration required to deactivate 50% of the enzyme (C-50) is dependent on logP(octanol) of the co-solvent. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Denaturation; Hydrophobicity; Polymer; Trypsin

Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin